2019
DOI: 10.15575/jpi.v4i2.1863
|View full text |Cite
|
Sign up to set email alerts
|

The Benefit of Islamic Faith Education to Enhance Children Social and Emotional Skills

Abstract: There is an increasing trend among parents nowadays to choose Islamic elementary school. This has triggered the increasing amount of schools that adopt religious bases such as Kuttab Al-Fatih (KAF), a school that emphasized manner education and Islamic faith teaching. The purposes of this study are to correlate Islamic faith education given by parents and student’s social and emotional skills and to compare children's emotional and social skills from parents whose children schooled in KAF and in other schools.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…Another study found that religious education makes a significant contribution to the mental health development of students (Estrada et al, 2019;Harianto et al, 2021;. A different conclusion was expressed by Sadida and Triman, from 52 respondents, there was no difference in the social and emotional skills of students studying at KAF and studying at other institutions (Sadida & Triman, 2019). Kuttab Alfatih is an educational institution that has a special curriculum for the religious field (Saugi, 2020).…”
Section: Introductionmentioning
confidence: 97%
“…Another study found that religious education makes a significant contribution to the mental health development of students (Estrada et al, 2019;Harianto et al, 2021;. A different conclusion was expressed by Sadida and Triman, from 52 respondents, there was no difference in the social and emotional skills of students studying at KAF and studying at other institutions (Sadida & Triman, 2019). Kuttab Alfatih is an educational institution that has a special curriculum for the religious field (Saugi, 2020).…”
Section: Introductionmentioning
confidence: 97%
“…The existence of early childhood education institutions is needed in guiding children to know Islam through Islamic religious learning. In addition, parents want to provide and equip their children with Islamic education (Sadida & Triman, 2019) Islamic religious learning in early childhood education is the most basic thing that needs to be introduced to early childhood (Harfiani, 2019). Islamic religious education for children after an early age is an effort to shape children to become devout adherents of human nature and become moral human beings, so that children are able to apply them in everyday life as obedient servants of Allah in reaching the life of the world and the hereafter (Hanipah, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The Qur'an has a very large role in children's basic learning which will be the foundation for character building in students which is the highest ideal of an Islamic educational institution (Colina & Listiana, 2021). A child who has good morals will be better able to control himself and also easier to learn other sciences (Sadida & Triman, 2019).…”
Section: Introductionmentioning
confidence: 99%